Digital divide: Mobile internet speeds in the Pacific - Amanda H A Watson (Asia Pacific Network, 2021)
This article outlines mobile internet speeds experienced by 15 smartphone users in the Pacific region. It presents new quantitative data collected over a six-month-long period. The data were collected in order to provide a comparison of places and to look for trends over time. The research was adjusted for confounding factors like weather and building type. The findings indicate substantial differences between the internet speeds and reliability experienced in Australian cities compared to the readings in Pacific Island locations. Over the six-month-long period, there were no substantial improvements or decreases in internet speeds at any of the included locations. This finding takes into account changes in weather, time of day and surroundings. As expected, clear skies and outdoor settings were positively associated with faster internet speeds, compared to rainy periods and indoor readings in the same geographical areas.